The Relationship between Job Satisfaction and Job Performance among Nursing Staff (Journal of Hama University, 2022)
The human element considers one of the most important production in the organization and the criterion for distinguishing between successful and failed institutions, which encouraged organizations of all kinds to focus on this element in order to achieve job satisfaction, which reflects positively on its performance and the whole performance of the organization.Aim:  - the aim of this study was to determine the relationship between job satisfaction and job performance among nursing staff at Tishreen University Hospital in Latakia city.Methods: a descriptive correlation quantitative study was performed using a convenience sample of (300) nurses from Tishreen University Hospital in Lattakia city. A structured questionnaire which developed by the researcher was used to collect data, it consisted of three dimensions: demographic variables, job satisfaction scale, and self- assessment of job performance scale using five-likert scale. the findings of this study showed that the - average level of job satisfaction, a high level of job performance, and strong positive statistical significant relationship between job satisfaction and job performance.the research concluded with some recommendations, the most important following up on procedures and practices that support job satisfaction, doing everything that would improve the level of job satisfaction with the nursing staff, following up their performance and analyzing it to determine strengths, identify weaknesses and study their causes to ensure the continued improvement of nursing staff’ performance level.